Construction of Selective Ion Transport Polymer at Anode–Electrolyte Interface for Stable Aqueous Zinc-Ion Batteries - Sun, Xuan; Lv, Xiaowei; Zhang, Man; Shi, Keqing; Li, Zhujie; Pan, Xinhui; Lian, Tong; Chen, Renjie; Wu, Feng; Li, Li (ACS nano, 2024)
Rampant dendrite formation and serious adverse parasitic reactions induced by migration of dissolved V/Mn cathode ions on Zn anode have hampered the high performance of aqueous zinc-ion batteries (AZIBs). Inspired by the coordination chemistry between functional groups of polymer and electrolyte ions, a freestanding layer consisting of dopamine-functionalized polypyrrole (DA-PPy) nanowires served as a selective ion transport layer at the anode–electrolyte interface to address these two issues, which could simultaneously avoid polarization caused by the introduction of an additional interface. On the one hand, the DA-PPy layer displays excellent zinc ion and charge transfer ability, as well as provides chemical homochanneling for zinc ions at the interface, which endow the DA-PPy layer with properties as a chemical guider and physical barrier for dendrite inhibition. On the other hand, the DA-PPy layer can trap excess transition metal ions fleeing from the cathodes, thus serving as a chemical barrier, preventing the formation of V x+/Mn x+-passivation on the surface of the zinc anode. Consequently, the AZIBs based on V2O5 and MnO2 cathodes involving the DA-PPy functional layer show a great improvement in the capacity retention.